The life of three Nicaraguan women on a coffee farm in Costa Rica (2008-2018): What they talked about during our reunions after 10 years - Shiode, Aya (2019)
This document reports a part of interviews conducted with three Nicaraguan migrant women in irregular situations, regarding their life and changes over the course of ten years between 2008 and 2018. The interviews were conducted during October and November 2018 on one of the main coffee cultivation areas in Costa Rica, Turrialba. The histories told by these three women show the difficult reality which surrounds them, but it also shows their courage and resilience in aiming for a dignified and hope-filled life.